Person Approach To Personal Passive In Standard Arabic* - Mohammed Shormani (Al-Lisaniyyat, 2017)
We develop a novel approach to personal passive in Standard Arabic (SA), building on 'implicit arguments' and the Person feature associated with the passive morphology (PM) attached to the verb. We propose that the PM is projected as a PassP (Passive Phrase), headed by Pass which has a Person (Prsn) feature which counts as an EPP feature. The article provides an Agree analysis of passive and the distribution passive arguments. We propose that both arguments are merged in their canonical positions:pro, i.e. the external argument, is merged as a specifier of vP, hence valuing its 0-role of agent and Case. Assuming that pro in personal passives is generic/indefinite, it is referentially 'weak, and thus it cannot value Pass's Prsn feature. Pass, then, probes for the only DP in its domain, i.e., the internal argument (or the (passive) syntactic sub- ject (henceforth, Syn-subj)), and triggers it to remerge in its Spec. It is also assumed that this 'remerging' is an A-movement, based on the fact that Spec-PassP is an A-position. In Spec-PassP, the Syn-subj values T's -features. T's EPP is assumed to be satisfied via V-raising to T.